Interscalable material microstructure organization in performance-based computational design - Yazici, Sevil (Frontiers of architectural research, 2024)
Various parameters can be integrated in material-based computational design in architecture. Materials are the main driver of these processes and evaluated with the constraints related to the form, performance, and fabrication techniques. However, current methodologies mostly involve investigating already existing materials. Studies on computational material design, in which new materials are developed by designing their microstructures in response to the performative issues, are generally undertaken at the material scale, and not adopted to the architectural design process yet. To resolve this issue, the methodology titled Interscalable Material Microstructure Organization in Performance-based Computational Design (I2MO_PCD) is developed and presented in three stages, including (1) identification of different types of material microstructures, (2) computational material design, and (3) prototyping. Data-based material modelling and visualization, and algorithmic modelling techniques are utilized, followed by various performance simulations as a part of an iterative process. New microstructure organizations are designed computationally, organized under three main groups as linear-curvilinear, crystal and metaball-voronoi. The outcomes of different performance analyses, including structure, radiation, direct sun hours, acoustics and thermal bridge were compared. Thus, the role of geometrical organization of microstructures, scales and material types in different performance computations were identified, by designing and fabricating synthetic materials.